ANALYSIS OF COMMODITY DISTRIBUTION PATTERN AND PRICE SETTING PATTERN - Dwi Kartikasari (Journal of Economics, Business, and Accountancy Ventura, 2010)
This paper concerns the distribution (marketing) channel behavior and price formation of commodities. It is a successive analysis answering question what commodities most contribute to inflation in Batam. These commodities are chicken meat, spinach, red chili pepper, string bean, water spinach (kangkung), mackerel (selar), and tuna fish (tongkol). The objectives of this research are (1) to break down the nature of marketing channel of commodities, i.e. chicken meat, spinach, and mackerel (selar); (2) to know the formation of selling price of the commodities. The research was conducted by purposive - snow ball sampling starting from producers.The respondents involved are 19 producers, 3 importers, 22 wholesalers, and 58 retailers. As a whole, the research proves that the common channel level is channel three for vegetables and chicken meat involving producers/importers, wholesaler, and retailers. Whereas the number of channel levels for fish is four since collectors (pengepul) gather from fishermen then bring the fish to wholesalers.